Promoting diaspora direct investments : Targeting investments made by the Finnish diaspora - Phillips, Sophia (My University, 2024)
This study aims to shed light on promoting diaspora direct investments, especially in the context of Finland. Movement between countries has been increasing, and according to estimations there are around 300 000 Finnish citizens and up to two million people of Finnish descent living outside of the Finnish borders. While the Finnish government has been placing increasing effort into engaging its diaspora abroad, there is still a gap in understanding their potential as investors and contributors to the national economy. Through gaining a better insight into the concept, this study wishes to motivate further exploration and action regarding the development and promotion of diaspora direct investment in Finland. The theoretical framework of the study builds on three main factors affecting its objectives. In order to understand promoting diaspora direct investments better, the study focuses on gaining a deeper view into the characteristics of diasporas, diaspora direct investments, and investment promotion. This study utilized qualitative methods to further enrich the theoretical framework and to tie the existing theories into the context of Finland. Five semi-structured interviews were conducted with relevant experts from Finnish institutions covering the topic of either diasporas or investment promotion. Findings of the study highlight the multiple different profiles of the Finnish diaspora and its heterogenous nature. The existing tie between the diaspora and Finland are seen as a possible driver in investment decision-making and an advantage after the investment-decision has been made. However, due to the complex nature of direct investment decision processes, it is left unclear whether these personal connections could overdrive the financial motives. Due to the relatively small size of the Finnish diaspora, it is unlikely that currently targeted international companies would have members of the Finnish diaspora in influential positions. This further highlights a different approach and a specialized strategy to promote direct investments specifically to the nation’s diaspora. The study suggests a few approaches to Finnish institutions based on previous theory and the study’s findings. These proposals emphasize the need for including, or at least acknowledging, diaspora direct investments in national diaspora and investment promotion strategies. Through applying some of the study’s findings, Finland can increase engagement with business-minded members of the diaspora internationally and start including them in the economic development of the country.

Tämä tutkimus pyrkii selvittämään diasporan tekemien suorien sijoitusten edistämistä, erityisesti Suomen kontekstissa. Maiden välinen liikkuvuus on lisääntynyt, ja arvioiden mukaan noin 300 000 Suomen kansalaista ja jopa kaksi miljoonaa suomalaistaustaista ihmistä asuu Suomen rajojen ulkopuolella. Vaikka Suomen hallitus on lisännyt ponnistelujaan ulkomailla asuvan diasporan sitouttamiseksi, on ymmärryksessä edelleen aukko heidän potentiaalisesta roolistansa sijoittajina sekä kansantalouden edistäjinä. Saamalla paremman käsityksen aiheesta, tämä tutkimus pyrkii motivoimaan jatkotutkimusta ja aloitteellisuutta diasporan tekemien suorien investointien kehittämiseksi ja edistämiseksi Suomessa. Tutkimuksen teoreettinen viitekehys rakentuu kolmen pääaiheen ympärille, jotka omalta osaltaan tukevat tutkimuksen tavoitteita. Suorien diaspora investointien edistämisen ymmärtämiseksi, tutkimus tarkastelee lähemmin diasporan ominaisuuksista, suoria diaspora investointeja sekä investointien edistämistä. Tutkimus hyödynsi laadullisia menetelmiä rikastaakseen teoreettista viitekehystä ja yhdistääkseen olemassa olevat teoriat Suomen kontekstiin. Tutkimusdata kerättiin puolistrukturoiduilla haastatteluilla viiden suomalaisen instituutin kanssa, joiden toimenkuvaan sisältyvät joko diasporaan tai investointien edistämiseen liittyvät asiat. Tutkimuksen tulokset korostavat suomalaisen diasporan moninaisia profiileja sekä heterogeenista luonnetta. Diasporan ja Suomen välinen yhteys nähdään mahdollisena vaikuttajana investointien päätöksenteossa sekä etuna investointipäätöksen tekemisen jälkeen. Investointipäätösten monimutkaisen luonteen vuoksi jää kuitenkin epäselväksi, voisivatko nämä henkilökohtaiset yhteydet ylittää taloudelliset motiivit. Suhteellisen pienen diasporan koon vuoksi on epätodennäköistä, että tällä hetkellä kohdennetuilla kansainvälisillä yrityksillä olisi suomalaisia diasporajäseniä vaikutusvaltaisissa asemissa. Tämä korostaa entisestään tarvetta uudelle lähestymistavalle sekä nimenomaan diasporalle kohdennetulle investointien edistämisen strategialle. Tutkimus ehdottaa muutamia lähestymistapoja suomalaisille instituutioille aiemman teorian ja tutkimuksen tulosten perusteella. Nämä ehdotukset korostavat tarvetta sisällyttää, tai ainakin tunnustaa, suorat diaspora investoinnit kansallisissa diaspora- ja investointien edistämisstrategioissa. Soveltamalla tutkimuksen tuloksia Suomi voi lisätä liiketoimintamielisten diasporan jäsenten sitouttamista kansainvälisesti sekä hyödyntää heitä maan taloudellisessa kehityksessä.
Keywords: diaspora direct investment, diaspora, FDI, investment promotion